Exploration of the Application of Balinese Local Wisdom in Handling Children with Autism - Ni Putu Sinta Dewi; Kadek Edi Yudiana; I Wayan Ardana (Universitas Pendidikan Ganesha, 2024)
Children with autism often experience difficulties in managing emotions, communication, and behavior, which can significantly impact their quality of life and social environment. The lack of culturally-based approaches in handling autism has become a barrier to creating interventions that align with local values and the children's cultural identity. This study aims to explore the application of local wisdom in the management of children with autism through structured and repetitive cultural activities. This research employed a qualitative method with a case study design. The research subjects consisted of 7 children with autism selected using purposive sampling techniques. Data were collected through participatory observation, structured interviews, and documentation, and then analyzed using thematic analysis techniques. The findings reveal that traditional cultural activities, such as making porosan, canang sari, and participating in religious rituals, have a positive impact on the development of fine motor skills, emotional regulation, and focus among children. Activities involving hand-eye coordination and repetitive processes foster mindfulness aspects that contribute to the children's calmness and self-regulation. Conceptually, this study implies the importance of integrating local wisdom values into culturally-based autism intervention programs to improve children's emotional well-being and motor skill development.